Curcumin Protects Osteoblasts From Oxidative Stress-Induced Dysfunction via GSK3β-Nrf2 Signaling Pathway - Li, Xumin; Chen, Yang; Mao, Yixin; Dai, Panpan; Sun, Xiaoyu; Zhang, Xiaorong; Cheng, Haoran; Wang, Yingting; Banda, Isaac; Wu, Gang; Ma, Jianfeng; Huang, Shengbin; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoblasts dysfunction, induced by oxidative stress (OS), is one of major pathological mechanisms for osteoporosis. Curcumin (Cur), a bioactive antioxidant compound, isolated from Curcumin longa L, was regarded as a strong reactive oxygen species (ROS) scavenger. However, it remains unveiled whether Cur can prevent osteoblasts from OS-induced dysfunction. To approach this question, we adopted a well-established OS model to investigate the preventive effect of Cur on osteoblasts dysfunction by measuring intracellular ROS production, cell viability, apoptosis rate and osteoblastogenesis markers. We showed that the pretreatment of Cur could significantly antagonize OS so as to suppress endogenous ROS production, maintain osteoblasts viability and promote osteoblastogenesis. Inhibiting Glycogen synthase kinase (GSK3β) and activating nuclear factor erythroid 2 related factor 2 (Nrf2) could significantly antagonize the destructive effects of OS, which indicated the critical role of GSK3β-Nrf2 signaling. Furthermore, Cur also abolished the suppressive effects of OS on GSK3β-Nrf2 signaling pathway. Our findings demonstrated that Cur could protect osteoblasts against OS-induced dysfunction via GSK3β-Nrf2 signaling and provide a promising way for osteoporosis treatment.